Prototype Sistem Pengering Gabah Otomatis Berbasis Arduino Uno Pada Kud Mattirobulu Desa Bontosunggu Kabupaten Bulukumba - Sukmawati sukmawati; Raden Wirawan; Juniarti iryani (Institut Teknologi dan Bisnis Bina Adinata, 2025)
Prototype of automatic grain dryer system using LDR sensor, Rain Sensor, RTC and Temperature Sensor as input variables to control the opening and closing of the dryer, stirrer and heater. Main control in this system is the Arduino Uno which uses the Microcontroller ATMega328. The cover for the grain dryer is connected to a rope that will be moved using a Motor Stepper. When the LDR sensor detects light and the rain sensor does not detect rain, the dryer cover will open. If the LDR sensor does not detect light and the rain sensor detects rain, the cover for the grain dryer will be closed. RTC is used for scheduling the time of grain stirring. The stirrer will move every 5 minutes. The temperature sensor is used to read the temperature, if the temperature is ≤50°, the incandescent lamp heater will be turned on. The whole system has been tested and runs as planned.